Խորհրդային Հայաստանի առաջին մանկավարժական թանգարանը - Ա. Շ. Սիմոնյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Идея создания педагогического музея всегда находилась в центре внимания передовой армянской общественности. Первая попытка основания при школе подобного музея была предпринята Хачатуром Абовяном. The idea of pedagogical museum foundation has always been in the centre of the Armenian advanced community attention. The first attempt to found such a museum attached to a school, was undertook by Khachatur Abovian.
Keywords: History; Museums; Collectors and collecting; D History; L Education